Adherence to Updated Childcare Nutrition Regulations in Colorado, United States - Eyler, Amy A.; Valko, Cheryl R.; Curoe, Katherine A.; Ramadas, Ramya; Chriqui, Jamie F. (Frontiers in Public Health, 2020)
Background: Preschool years are an important time for shaping healthy eating behaviors. Childcare centers can be a venue for policy change for broad and sustained positive impact on healthy eating environment. The objective of this study was to assess how self-reported current practices align with updated statewide childcare center licensing regulations in Colorado, US. Methods: Using a post-test only study design, a survey was sent to all full-day, licensed childcare centers in Colorado (N= 1398) with a valid street or email address. The survey included questions on allowable food and beverages, mealtime practices, and perceptions of the updated regulations. Frequencies were calculated and logistic regression models computed for a composite score of each of these factors. Results: Respondents (N= 343) were mostly center directors, with over eight years of experience, from urban areas. Compliance was high for most food and beverage criteria (over 90%) and all meal practices. One third participated in the federal Child and Adult Care Food Program (CACFP), and were more likely to comply with the state meal regulations than non-CACFP centers. Conclusion: Although our results show high self-reported compliance, a more thorough study of the policy process would provide comprehensive evidence on effective development, enactment, and implementation of these regulations.